Essays on geography and diseases - Esposito, Elena <1983> (Alma Mater Studiorum - Università di Bologna, 2014)
This dissertation explores how diseases contributed to shape historical institutions and how health and diseases are still affecting modern comparative development. The overarching goal of this investigation is to identify the channels linking geographic suitability to diseases and the emergence of historical and modern insitutions, while tackling the endogenenity problems that traditionally undermine this literature. I attempt to do so by taking advantage of the vast amount of newly available historical data and of the richness of data accessible through the geographic information system (GIS).